2009
DOI: 10.1111/j.1365-2850.2009.01420.x
|View full text |Cite
|
Sign up to set email alerts
|

Insights from inside: the duties and activities of nurses at the psychiatric clinic Münsterlingen (CH). A qualitative study

Abstract: In the German-speaking countries: Austria, Germany and Switzerland, which have a joint annual conference in psychiatric nursing, the process of academization of nursing has led to a discussion about which adaptations to make in psychiatric nursing in order to develop a profile, which is practicable in the future. Therefore, it was necessary to describe the current duties and activities of psychiatric nurses. With this, the knowledge and abilities of the nurses were to be made more explicit and their identity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…This is in contrast to Magnusson et al (2004) study where MHNs were reported to assume paternalistic roles to fulfil perceived duties to services and service users. MacNeela et al (2010) in their Delphi study on essential elements of MHN care found the coordination, organization, and communication of care was a core role of the MHN, as did Schoppmann and L€ uthi (2009) in their observational study on the roles of the in-patient MHN. Similar capabilities were found by Cleary (2003) where simultaneous demands of decision-making and prioritizing multiple tasks were core MHN roles.…”
Section: Non-technical Mhn Rolesmentioning
confidence: 93%
“…This is in contrast to Magnusson et al (2004) study where MHNs were reported to assume paternalistic roles to fulfil perceived duties to services and service users. MacNeela et al (2010) in their Delphi study on essential elements of MHN care found the coordination, organization, and communication of care was a core role of the MHN, as did Schoppmann and L€ uthi (2009) in their observational study on the roles of the in-patient MHN. Similar capabilities were found by Cleary (2003) where simultaneous demands of decision-making and prioritizing multiple tasks were core MHN roles.…”
Section: Non-technical Mhn Rolesmentioning
confidence: 93%
“…They take care of patients’ basic needs, for example feeding and personal and environmental hygiene. Furthermore, they are responsible for dispensing and administration of medication and participate in the patients’ therapy by creating a stimulating environment (Schoppmann & Lüthi 2009 ). Nurses are often subjected to violent and aggressive behaviour from patients (Currid 2009 ) and experience pressure created by inadequate resources, such as staff and bed shortages (Currid 2009 ; Mann & Cowburn 2005 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, the participants had no concrete ideas concerning the strengthening of these elements via RO interventions. By contrast, protecting and preserving a patient’s identity is described as a central element for mental health nursing in a very common textbook ( 56 ) in German-speaking countries, and there is evidence that suggests that nurses tend to pursue these tasks in a rather unconscious manner ( 57 ). In the focus groups, the demand for a more active “resource orientation” might be seen as an implicit way to strengthen a patient’s identity since such a mode of working has to focus on competencies and activities that have a positively connoted personal meaning for them.…”
Section: Discussionmentioning
confidence: 99%